Local Culture: Curation as an Ethnographic Process in the Contemporary Cuban Art Scene - Celia Irina González (Íconos)
This study contributes to the discussion on the production of anthropological knowledge and the visual arts in particular fields such as design, installation and curation. The fieldwork was conducted in La Habana under the guise of the practice of curation as a site of ethnographic practice, method and theory building. In concrete terms, the study centres on an exhibition called Cultura Autóctona, with the objective of understanding the contemporary Cuban art scene and its repercussions for the production of practices involved in its politically critical social context. The design of the exhibition and curation process has contributed elements to the current debate within visual anthropology: understanding of the image as a process of inter-relation, more than of description.